Environmental preservation through post-tin mining land reclamation in Sukamandi Village, East Belitung - Hartini Hartini; Almasy Tsalisa Haiba; Erwin Erwin; Yogi Yogi; Febi Deya Safitri; Gayuh Ageng Munawwaroh; Muhamad Donny Sudrajat; Rika Novebri Putri; Fachrurrozy Purwadinata; Muayyadah Milla; Wiwi Jales W; Putra Ramadhani Said; Muhammad Eka Mardyansyah Simbolon (Universitas Muhammadiyah Magelang, 2023)
Exploitation efforts through mining can have severe environmental impacts, including damage to ecosystems, pollution of clean water sources, as well as social and health consequences. This is precisely what occurred in Sukamandi Village, Damar Subdistrict, East Belitung District, where the land was adversely affected by tin mining activities. This community service program aims to empower Pokdarwis Sukma Beransai in implementing post-tin mining reclamation as a means of environmental preservation and raising community awareness. The program involves activities such as socialization and mangrove planting on former tin mining sites. The outcome of this program includes heightened public awareness and improved understanding of environmental conservation, as well as the recognition of tourism potential that can support economic development.